Evaluation of the agronomical behaviour of different oregano ecotypes in 25 de mayo, La Pampa (Semiárida, 2018)
Oregano is cultivated in semiarid regions with a negative water balance, therefore is necessary to apply irrigation according water needs. The area of 25 de mayo, La Pampa, which is fed by the Río Colorado, has an irrigation system that makes it suitable for this kind of farming. The goal of this paper was characterize productivity of four oregano ecotypes (Criollo, Mendocino, Cordobés and Compacto) in the irrigated area of 25 de Mayo. Dry matterin flowers and leaves of each ecotype was determined. The results showed that there were no significant differences in yield (p=0.05). However, it should be highlighted that important differences could be observed in the field where, Criollo and Cordobés ecotypes had highest productivity. The yield obtained was highest than in traditional areas, such as Mendoza and Córdoba, which makes the region under study a promising option for oregano production. DOI: http://dx.doi.org/10.19137/semiarida.2016(01).35-42
Keywords: Origanum; yield; ecotype; production area